Foreign direct investment and growth: analysis of the construction sector in the Baltic States - Banaitienė, Nerija; Banaitis, Audrius; Laučys, Mindaugas (Journal of Civil Engineering and Management, 2015)
In the construction industry of the Baltic States, the aftermath of the economic crisis poses new questions as to what occasioned the crisis. The paper analyses a causal relationship between foreign direct investment in construction (CFDI) and the contribution of the construction industry to gross domestic product (GDP) using data obtained in the Baltic States (Lithuania, Latvia and Estonia) for the period from 2000 to 2011. The conducted research includes the initial econometric analysis of variables, which involves the verification of seasonality and stationarity with the help of time series plots, a unit root test and Granger causality test. The study has found that, in the case of Lithuania and Estonia, CFDI is not the Granger cause of the construction industry’s contribution to GDP growth; conversely, value added by the construction sector is not the Granger cause of FDI into the sector, and there is one-way causality from value added by the construction sector to CFDI, and the construction industry’s contribution to GDP does not influence CFDI in Latvia.